2015
DOI: 10.1136/bjsports-2014-094570
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided hip joint injections are more accurate than landmark-guided injections: a systematic review and meta-analysis

Abstract: This is the first systematic review and meta-analysis of the accuracy of US-guided versus landmark-guided hip joint injections that has revealed that US-guided injections are significantly more accurate than those that are landmark guided. Future studies should compare US with fluoroscopic-guided hip joint injections for accuracy, efficacy, safety profile, cost-effectiveness and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…In a randomised, double-blind, controlled study of ultrasound-guided versus palpation-guided corticosteroid injection into various joints in patients with inflammatory arthritis, Cunnington et al 9 demonstrated that despite substantially improved accuracy with ultrasound guidance, short-term outcomes were not significantly different. This is contrasted by the AMSSM position paper3 that concluded moderate evidence for improved efficacy with ultrasound-guided injection, which highlights the need for further outcome-based studies. Safety factors should also be taken into account, as improved accuracy with US guidance may lead to reduced neurovascular injury, skin depigmentation, subcutaneous fat atrophy, intra-arterial injection, as well as pain and discomfort.…”
Section: Efficacy and Safetymentioning
confidence: 83%
See 2 more Smart Citations
“…In a randomised, double-blind, controlled study of ultrasound-guided versus palpation-guided corticosteroid injection into various joints in patients with inflammatory arthritis, Cunnington et al 9 demonstrated that despite substantially improved accuracy with ultrasound guidance, short-term outcomes were not significantly different. This is contrasted by the AMSSM position paper3 that concluded moderate evidence for improved efficacy with ultrasound-guided injection, which highlights the need for further outcome-based studies. Safety factors should also be taken into account, as improved accuracy with US guidance may lead to reduced neurovascular injury, skin depigmentation, subcutaneous fat atrophy, intra-arterial injection, as well as pain and discomfort.…”
Section: Efficacy and Safetymentioning
confidence: 83%
“…The AMSSM position paper3 concluded that there was preliminary evidence in favour of improved cost-effectiveness for ultrasound-guided injection for large joints and inflamed joints.…”
Section: Efficacy and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…The supremacy of ultrasound guidance over so-called blind injection techniques has been established at virtually all anatomical locations. [9][10][11][12] The use of ultrasound-guided injections in the athletic population is therefore increasing, most of which is attributed to nonradiologists, predominantly sports medicine physicians, 13 for whom ultrasoundguided procedures form an important part of formal training. 14 Radiologists, however, have a greater overall procedural foundation, including the use of other imaging modalities for guidance, that may be more suitable in certain anatomical locations.…”
Section: Role Of the Musculoskeletal Radiologist: Team Playermentioning
confidence: 99%
“…A position statement by the American Medical Society for Sports Medicine reviewed the literature and found several level one studies of ultrasound guided hip injections with a mean accuracy of 99% [11]. In addition, a recent meta-analysis revealed that ultrasound-guided hip joint injections were significantly more accurate than landmark-guided intra-articular hip injections (accuracies were 100%, 95%CI 98–100%; 72%, 95%CI 56–85%, respectively) [12]. …”
Section: Ultrasound-guided Injection For Specific Anatomic Hip and Grmentioning
confidence: 99%